SOIL ARTHROPODS COMMUNITY IN COFFEE PLANTATION (COFFEA ARABICA) AT TWO DIFFERENT CONDITION IN PALINTANG â WEST JAVA - Kristin, Marcellina
Soil arthropods community is important in maintaining soil condition and is sensitive to environmental factors. Good soil conditions are important in the plantation sector because it will affect the productivity. Coffee is one of the most important plantation commodities in Indonesia. The increase in domestic demand is not proportional to the production of cofee comodities. One of the causes of the non-optimal productivity is a decrease in soil quality. The purpose of this study was to examine the community of soil arthropods on land that was given different treatment in a coffee plantation (Coffea arabica) Palintang, Bandung Regency, West Java. The lands are named as Land A and Land B. Land A is a coffee plantation area that is cleared from weeds, while Land B is one that is not cleared from weeds. The study was conducted from August-December 2020. Air climatic data was measured with a logger and soil edaphic was measured with a soil tester. Sampling of soil arthropods was carried out using a pitfall trap. Pitfall traps were installed three times during the research period, one time each in September, October, and December. For each arthropod sampling, 5 sets of pitfall traps were installed in each Land A and Land B with one set of pitfall traps consisting of 5 traps. The results showed that the conditions of air temperature, light intensity, soil pH, and soil moisture were not significantly different between Land A and Land B. The difference in environmental conditions is obtained from determining the criteria for soil chemical properties and air moisture conditions. There were 10 orders of soil arthropods consisting of 64 morphospecies and 688 individuals in Land A and 14 orders consisting of 71 morphospecies and 873 individuals of soil arthropods in Land B. The diversity index (H') in Land A was 2.443 (D=0.207; E). = 0.587) and lower than Land B with a value of 2.602 (D = 0.201; 0.610). The orders Dernaptera, Psocoptera, and Polydesmida were only found in Land B, indicating that Land B was more humid than Land A. The difference in soil arthropod communities in the two fields could be due to the nutrient content in the soil and different vegetation conditions between the two fields. Soil arthropod diversity will be higher in soils with good quality and diverse vegetation. Higher soil arthropod diversity indicates a more stable arthropod community. Weed pruning affected the soil arthropod community in both fields.